Struktura ryzyka audytowego a wybór próby - kilka uwag praktycznych - Staszkiewicz, Piotr (Audit Risk Structure and Sample Selection - Some Practical Remarks, 2005)
The author discusses the practical method for the sample selection. Some basie hints are shown for the sample selection and results approximation. A specific heuristic method used AKF Ltd has been described in details.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 166-170